(untitled) (Medico Legal Update, 2020)
The ability to pay and the willingness to pay is a contributing factor in the utilization of services. The population in this study was a general patient who was educated at a psychiatric clinic in the Special Hospital of Maluku Province, 2019. The samples in this study are common patients who are given services to psychiatric clinics. The number of samples obtained using accidental sampling techniques obtained as much as 48 people. The results showed that patients could pay (Abilitiy to Pay) at psychiatric clinics at a rate of Rp. 80,000 with the ability to pay a maximum of Rp. 175,000 and the ability to pay a minimum of Rp. 40,000 whereas the willingness to pay (willingness to pay) normative patients at the Special Hospital Psychiatric Clinic of Maluku region is Rp. 82,083 with a willingness to pay a maximum normative amount of Rp. 100,000 and a willingness to pay a minimum normative cost of Rp. 75,000. Hospitals can revise tariffs in psychiatric clinics taking into account the level of ability and willingness of the community and set rates that do not exceed the ability to pay the community.